2017
DOI: 10.1039/c6tb03317b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-tuned nanozyme polymerization for the preparation of hydrogels with printable and antibacterial properties

Abstract: A printable, antibacterial polymer hydrogel was prepared by a nanozyme catalyzed radical polymerization under physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Various nanozyme based applications have been extensively explored, including in vitro and in vivo biosensors, and antibacterial and disease therapies, such as cancer theranostics, bone marrow therapy, and wound healing . In addition, environmental protection is also an important area.…”
Section: Applications Of Nanozymesmentioning
confidence: 99%
“…Various nanozyme based applications have been extensively explored, including in vitro and in vivo biosensors, and antibacterial and disease therapies, such as cancer theranostics, bone marrow therapy, and wound healing . In addition, environmental protection is also an important area.…”
Section: Applications Of Nanozymesmentioning
confidence: 99%
“…In a study, researchers prepared poly(DMAA‐cross‐BIS) hydrogel using peroxidase‐mimic CuO NPs. [ 218 ] Along with the direct gelation initiated by CuO nanozymes, it has been shown that fluorescent polydopamine can be synthesized via Fe 3 O 4 catalysis. [ 219 ] With improved physicochemical properties, nanozymes are expected to draw in expertise from diverse disciplines in the future and emerge as a new field of research in nanobiotechnology.…”
Section: Nanozymesmentioning
confidence: 99%
“…Interestingly, the catalytic activity of CuO NRs showed significant catalytic enhancement under visible light irradiation, allowing light control of antibacterial activity. 138,139 Nanoceria has a variety of enzymic properties. A nanoceria was discovered with both CAT and SOD properties, which was controlled by the Ce 3+ /Ce 4+ ratio.…”
Section: Nanozymes As Antimicrobial and Antifouling Agentsmentioning
confidence: 99%